Changes in topsoil characteristics with climate and island age in the agricultural zones of the Galápagos - Dinter, Tamara C.; Gerzabek, Martin H.; Puschenreiter, Markus; Strobel, Bjarne W.; Strahlhofer, Matthias; Couenberg, Paulina M.; Zehetner, Franz (Geoderma, 2020)
•Particle size and soil organic carbon decreased with increasing weathering duration.•Al and Fe accumulated in older, highly weathered soils while base cations decreased.•Andic properties were expressed in the youngest soils studied.•Andic properties increased with elevation / moisture. The flora and fauna of the Galápagos Islands have long been subject to scientific inquiry, but the soils have remained largely ignored until recently. The objective of this study was to assess the differences in main soil characteristics and nutrient reserves within and among the agricultural zones of islands Isabela, Santa Cruz and San Cristóbal to provide background information for informed agricultural decision making and a baseline against which future changes may be assessed. Aqua regia-extractable Al and Fe showed a general trend of accumulation with island age and increasing moisture levels within the agricultural zone, while base cations Ca, K, Mg and Na tended to decrease along the same gradients, with some variation likely due to agricultural inputs. Concentrations of silicon, aluminum and iron associated with amorphous constituents (Sio, Alo, Feo) tended to decrease with island age while iron in crystalline and non-crystalline hydrous oxides (Fed) showed a slight increase. Aluminum and iron in non-crystalline and organic complexes were more abundant in areas with higher precipitation. Electrical conductivity, pH in water, pH in sodium fluoride, phosphate retention, organic carbon content and particle size tended to decrease with island age while bulk density increased. Andic properties were expressed in all the soils of the youngest island studied, Isabela, and in higher-elevation soils of the intermediate-age Santa Cruz Island, while the soils of the oldest island studied, San Cristóbal, did not show andic properties and were dominated by crystalline clays and iron oxides. The wide range of soil development across the three islands requires soil management recommendations be tailored to each island and even within each island to ensure appropriate stewardship of this important natural resource.